2021
DOI: 10.1111/nhs.12838
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of a mindful resiliency program for community healthcare providers

Abstract: Despite the important contribution of nongovernmental organizations (NGOs) to the community healthcare sector, the building and maintenance of occupational resilience in community health workers has received little attention. However, it is recognized that employees in this sector are exposed to significant stressors from the high demand work environment which negatively impacts on their well‐being. Therefore, this research examined the acceptability, feasibility, and sustainability of a mindful resiliency pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In conclusion, our study underlines the negative effects of the COVID‐19 pandemic on the psychological well‐being of frontline healthcare workers, which can lead to emotional exhaustion and increased risk of burnout. Moreover, this study suggests that intervention policies should include strategies to promote resilience (see, for example, Klockner et al, 2021; Heath et al, 2020) and the development of stress management practices to identify working conditions that cause the most job dissatisfaction (Neto et al, 2020). These findings are relevant in order to protect the health of professionals who are caring for patients in different waves of COVID‐19 or similar emergency situations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, our study underlines the negative effects of the COVID‐19 pandemic on the psychological well‐being of frontline healthcare workers, which can lead to emotional exhaustion and increased risk of burnout. Moreover, this study suggests that intervention policies should include strategies to promote resilience (see, for example, Klockner et al, 2021; Heath et al, 2020) and the development of stress management practices to identify working conditions that cause the most job dissatisfaction (Neto et al, 2020). These findings are relevant in order to protect the health of professionals who are caring for patients in different waves of COVID‐19 or similar emergency situations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, employees with low levels of job satisfaction are most likely to experience emotional burnout, to have reduced levels of self‐esteem, and to have raised levels of both anxiety and depression. Therefore, a supportive work environment is vital to promoting resilience and the job satisfaction of clinicians during an emergency such as COVID‐19 (Faragher et al, 2005; Klockner et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, after the onset of COVID-19, mind–body practices have been proposed and evaluated to improve the psycho-emotional status of HCPs, including perceived stress, demonstrating their acceptance by HCPs, feasibility and effectiveness [ 13 , 14 ]. Since professionals with low levels of job satisfaction are more likely to experience distress (e.g., anxiety and depression), a supportive work environment is crucial to promote resilience and job satisfaction, providing the highest standard of care in the safest possible environment, especially during an emergency such as COVID-19 [ 15 , 16 ]. Indeed, MBSR can help HCPs to improve interpersonal relationships with patients and colleagues, to take better care of themselves and others, to pay more attention to the present moment, developing concentration and consequently improving work performance, being more available to listen and more motivated.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of 20 community service workers in Australia found that participation in a mindfulness-based intervention program increased their perceived ability to cope with the COVID-19 pandemic ( Klockner et al, 2021 ). Similarly, in a sample of 38 HCWs, completing an online resilience training program resulted in decreased emotional distress at months one and two and increased resilience 2 months postintervention ( DeTore et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%